Optimizing Traditional Public Space Through Agent-Based Simulation: "A Case of Lagan Chowk" - Karan, Bhushan; Uprety, Sanjaya (Journal of Engineering Issues and Solutions, 2026)
Rapid urbanization in the Kathmandu Valley has reshaped the functioning of public spaces within dense historic settlements. Increasing population pressure, land encroachment, and infrastructure- oriented development have reduced their spatial quality and social relevance. Although many traditional courtyards and squares still remain, their capacity to support daily movement, informal gathering, and community activities has gradually declined. Public space is often treated as a fixed physical form, and conventional planning tools largely limited to static, two-dimensional drawings fail to reflect the dynamic and lived nature of these environments. This study conceptualizes public space as a dynamic system shaped by movement, behavior, and temporal variation. It adopts a data-informed design framework integrating field observation, space-syntax analysis, and agent- based simulation to examine movement patterns and spatial performance in Lagan Chowk, of Kathmandu Metropolitan City. The findings show that spatial vitality varies across time periods and that movement is structured not only by configurational accessibility but by programmatic anchors such as markets, temples, and social nodes. A persistent conflict between pedestrian movement and vehicular access is also identified, particularly in areas modified for ritual use.The study demonstrates that accessibility alone does not ensure activity and proposes incremental, context-sensitive interventions to improve usability while preserving cultural structure.